Identification of best performer hilly chickens of Bangladesh in consideration of climate change factors: light and heat - KHAN, M K I; SIDDIKI, AMAM Z; ALI, M R; AKTER, M A (The Indian Journal of Animal Sciences, 2017)
The best performer hilly chickens in consideration of light and heat were assessed under rural conditions. Based on the survey, the chickens and farm household were selected. The chickens were provided supplementations of concentrate feed (50g/chicken/day). The selected chickens were divided into 3 groups (heat stress, light and control) for the study of their egg production potential. Heat was generated in the chicken's shelter by keeping a black shaded light (Lantern) for 2 to 3 h more after sunset. A lighting device (Lantern) was kept in the chicken's shelter for 2 to 3 h more after sunset for increasing the duration of day light. Temperature and humidity index was calculated from the recorded temperature and humidity. The individual chicken's egg production, egg weight and mature live weight were studied for different types of hilly and non-descriptive desi chickens. It was observed that hilly chickensproduced more eggs than desi. The hen house egg production percentage (19.95%) and yearly egg production (90no/year/chicken) of desi white was significantly higher than spotted hilly (17.29% and 83.4 no egg, respectively) but reddish brown hilly type produced more number (100.80 no/year/chicken) of eggs than all types. The egg weight varied from 41.27 g to 43.85 g. Mature live weight were significantly different between hilly and desi(1438.70 g vs 1309.27 g). Among the 3 treatments, the lighting group hilly chickens produced 7.71 and 5.60 more eggs than control and heat stress group, respectively. One hour lighting length increased egg production by 4 to 5.8%.